Investigación “análisis de la influencia de Facebook en la identidad de los adolescentes de 16-18 años de la facultad de psicología Universidad Antonio Nariño” (2017)
Social networks are aimed at guiding society to a world, with and without foundation, Facebook, a social network that was created at the beginning to interact among students of a university, was growing so much and has become one of the networks more used by young people, thanks to that contacts are maintained, friendships are cultivated, but also Facebook is used to get to influence the ideology of those who are just seeking autonomy, could not go against technology, but know how to handle and be decisive when leaving or not influence by the information that can be accessed on Facebook. Through a quantitative research, an analysis was made of the influence of Facebook on the identity of adolescents, using an interview focused on 5 items of attention that are: social identity, social categorization, social comparison, affectivity and influence of use, in order to obtain a high degree of relevant information about this network.